The voters perception of election issues unique to Sabah in Likas / Amy Sulastri Sulaiman and Shafwanah Farhanah Apil - Sulaiman, Amy Sulastri; Apil, Shafwanah Farhanah (2012)
This research aims to examine the general perception of voters on the issues in the N:14 Likas election. In particular, this study was conducted to identify key issues in the election. Among the areas of focus are information, knowledge and perceptions of voters and others criteria which are seen as vital in assessing the perceptions of voters. The main objective of this study is to examine the voter's perception towards the election issue in Sabah. The a methods that have been use are qualitative and quantittive. A judgement sampling types of purposive sampling in determining our sample of 100 respondents which involved in this study. The finding shows the pattern of perception, voting behaviour and the election issues that unique to Sabah among the voters especially in Kg. Likas.